2015
DOI: 10.9734/ijmpcr/2015/19187
|View full text |Cite
|
Sign up to set email alerts
|

Hibernoma at Base of Neck- A Rare Case in a Six Month Old Infant

Abstract: Hibernomas are very uncommon soft tissue tumors. They are composed of brown fat. They are usually seen in adults in the fourth/ fifth decades according to published literature. Very few cases in Paediatric age group have been reported. We present a hibernoma presenting as a swelling on the posterior aspect of base of neck in a six month old infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It may persist in certain areas such as neck, axilla, periaortic area, mediastinum, and perirenal areas. [8] The function of this brown fat is to promote nonshivering thermogenesis. [1] On thorough literature search, we found that <20 cases of cervical hibernoma have been reported till date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may persist in certain areas such as neck, axilla, periaortic area, mediastinum, and perirenal areas. [8] The function of this brown fat is to promote nonshivering thermogenesis. [1] On thorough literature search, we found that <20 cases of cervical hibernoma have been reported till date.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] Most common anatomical locations were the thigh shoulder, back, neck, chest, arm, and abdominal cavity. [8] Diagnostic imaging studies are invaluable in the preliminary diagnosis of fatty tumors. [2] Plain X-rays and computed tomography (CT) scan can suggest the fat density of the tumor.…”
Section: Discussionmentioning
confidence: 99%